Deep genomic analysis of the Chlorella sorokiniana SAG 211-8k chloroplast. Issue 3 (3rd July 2017) - Malavasi, Veronica; Costelli, Cristina; Orsini, Massimiliano; Cusano, Roberto; Angius, Andrea; Cao, Giacomo
Abstract: The chloroplast genome contains information that is applicable in many scientific fields, such as plant systematics, phylogenetic reconstruction and biotechnology, because its features are highly conserved among species. To date, several complete green algal chloroplast genomes have been sequenced and assembled. In this study, the nucleotide sequence of the chloroplast genome (cpDNA) of Chlorella sorokiniana SAG 211-8k is reported and compared for the first time to the chloroplast genomes of 10 Chlorellaceae. The recently updated Chlorella sorokiniana cpDNA sequence, assembled as a circular map of 109 811 bp, encodes 113 genes. Similar to other Chlorella strains, this chloroplast genome does not show a quadripartite structure and lacks the large rRNA operon-encoding Inverted Repeat (IR). The Chlorella sorokiniana plastid encodes the tRNA(Ile)-lysidine synthetase ( til S), which is responsible for modifying the CAU anticodon of a unique tRNA. Gene ordering and clustering highlight the close relationships among Chlorella clade members and the preservation of crucial gene clusters in photosynthetic strains. The features of Chlorella sorokiniana presented here reinforce the monophyletic character of Chlorellaceae and provide important information that sheds light on chloroplast genome evolution among species of Chlorella .